Cervical Anatomical Landmarks Indicate the Amount of Vertebra Resection during ACAF Surgery: A Semi‐Quantitative Anatomical Parameter Study on Imaging Data - Pang, Qingyang; Ling, Shiyong; Zhang, Bin; Zhu, Jian; Sun, Jingchuan (Orthopaedic surgery, 2022)
Objective With the innovation and development of cervical spine surgical procedures, there is currently a lack of new and reliable data on cervical anatomical landmarks. The purpose of this study is to measure the CT data of the cervical vertebrae of healthy volunteers, so as to make up for the missing part of the measured value of cervical vertebra bone markers, and provide data support for the safety and accuracy of anterior controllable antedisplacement and fusion (ACAF) surgery. Methods From January 2019 to January 2020, the cervical computed tomography (CT) scan image data of volunteers in Changhai Hospital and Zhabei Hospital were randomly selected. The radiological parameters included three parameters were measured in the upper lamina plane. a: the distance from the anterior edge of the vertebral body to the anterior edge of the bilateral uncinate joint; c1: the sagittal diameter of the vertebral body; and d: the distance between the anterior edge of the uncinate joint. Three parameters were measured in the pedicle plane. b: the vertical distance from the anterior edge of the vertebral body to the junction line between the two lateral processes; c2: the sagittal diameter of the vertebral body; e: the transverse diameter of the vertebral body; and f: the sagittal diameter of the vertebral canal. The correlation ratios were calculated: a/c1, b/c2, a/f, b/f, d/e. The data between the two groups were compared by independent sample t‐test. Results Finally, 51 patients were included in this study, 18 males and 33 females, with an average age of 47.9 years (21–72 years). The maximum values of seven parameters measured were all at C7. The minimum b value was at C5, and the minimum f value was at C4. The minimum values of the other five parameters were all at C3, and there was an increasing relationship from C3 to C7 (P < 0.05). There was significant difference between male and female with regard to c1, c2, e and d values (P < 0.05). No significant differences were observed between men and women regard to the ratio of related parameters (a/c1, b/c2, a/f, b/f, d/e). Conclusions Anatomical consideration of this area is useful to estimate amount of vertebral body resection when performing the bony cut made in ACAF surgery; however, pre‐operative examinations with appropriate radiographic analysis are also recommended. There was significant difference between male and female with regard to c1, c2, e and d values (P < 0.05). No significant differences were observed between men and women regard to the ratio of related parameters (a/c1, blc2, a/f, b/f, d/e).